A catalyst for preparing acrylonitrile by propylene ammoxidation, and its preparation method and application

By using a catalyst composed of oxides of three active metal elements, Mo, Bi, and Fe, and a silicon-based porous support, the problems of complex catalyst preparation and poor activity stability in the prior art are solved, and high stability and long-term operation activity maintenance are achieved.

CN116060028BActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111300847.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-04
Publication Date
2025-04-29
Estimated Expiration
2041-11-04

AI Technical Summary

Technical Problem

In the prior art, the catalyst for preparing acrylonitrile by acrylic ammonia oxidation requires the combination of multiple metal elements, resulting in complex preparation process, difficult to guarantee activity and stability, and short operation cycles.

Method used

A catalyst composed of metal oxides and silicon-based porous support, including oxides of three active metal elements: Mo, Bi and Fe, is ensured through specific preparation methods and calcination processes, and the high stability of the catalyst and long-term operation activity are maintained.

Benefits of technology

The high stability of the catalyst and the activity of long-term operation are achieved, and the one-way yield and conversion rate of acrylonitrile remain high after long-term operation, avoiding the problem of decreasing catalyst activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060028B_ABST
    Figure CN116060028B_ABST
Patent Text Reader

Abstract

The present invention discloses a catalyst for preparing acrylonitrile by ammoxidation of propylene, a preparation method thereof, and an application thereof. The catalyst of the present invention comprises a metal oxide and a carrier component. The carrier component is a silicon-based porous carrier. The metal oxide comprises at least oxides of three active metal elements, namely Mo, Bi, and Fe. The specific surface area of the catalyst is 60-100 m² / g, and the average pore diameter is 5-10 nm. In the infrared spectrum of the acrylonitrile catalyst, there are no characteristic peaks in the range of 2800 cm⁻¹ to 3000 cm⁻¹. In the preparation method of the present invention, the prepared catalyst precursor particles are mixed with peroxide particles and then calcined. The acrylonitrile catalyst of the present invention has high stability and can still maintain good activity and selectivity after long-term operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a catalyst for preparing acrylonitrile by ammoxidation of propylene and a preparation method thereof, as well as application of the catalyst in preparing acrylonitrile by ammoxidation of propylene. Background Art

[0002] Acrylonitrile (AN) is a very important basic organic raw material, which can be used for synthetic fiber acrylic, and is also the raw material for thermoplastic synthetic resins such as acrylonitrile-butadiene-styrene (ABS), styrene-acrylonitrile (SAN), nitrile rubber, adiponitrile, acrylamide and other derivatives. At present, the process technology of producing acrylonitrile by propylene ammoxidation has become increasingly mature, among which the catalyst is the technical core of the process. The development of catalysts with excellent performance for preparing acrylonitrile by propylene ammoxidation is a hot topic in the acrylonitrile industry.

[0003] CN102371156A discloses a fluidized bed catalyst for preparing unsaturated nitrile by ammonia oxidation and a preparation method thereof. The catalyst uses silica sol as a carrier and needs to introduce Zr, Ti or Th, which effectively prevents the sintering process of the catalyst. The catalyst has good acrylonitrile selectivity and relatively stable acrylonitrile per-pass yield at a temperature of about 430°C.

[0004] CN109772356A discloses an acrylonitrile catalyst and its preparation method and application. The catalyst contains molybdenum, bismuth, nickel, magnesium and iron as essential components, and the activity and selectivity of the catalyst are improved mainly by reasonably matching the elements and giving full play to the synergistic effect between the elements.

[0005] CN105195165A discloses a fluidized bed catalyst for preparing unsaturated nitriles by ammoxidation of olefins and a preparation method thereof. The method obtains precursor slurries with different pH values ​​under different stirring and precipitation times, so that cerium oxide is evenly distributed on the surface of the acrylonitrile catalyst, thereby improving the oxygen storage and release capacity of the catalyst and increasing the acrylonitrile yield.

[0006] In the above technical solutions, the catalysts for preparing acrylonitrile by propylene ammoxidation mostly need to be coordinated with multiple metal elements. How to prepare a catalyst for preparing acrylonitrile with good activity and stability by a simple method, so as to improve the operation cycle of the catalyst, has always been a problem to be solved in the art. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a catalyst for preparing acrylonitrile by propylene ammoxidation, a preparation method and application thereof. The catalyst has high stability and can maintain good activity and selectivity after long-term operation.

[0008] The first aspect of the present invention provides a catalyst for preparing acrylonitrile by propylene ammoxidation, the catalyst comprising a metal oxide and a carrier component, the carrier component being a silicon-based porous carrier, the metal oxide comprising at least oxides of three active metal elements, namely, Mo, Bi, and Fe, and the specific surface area of ​​the catalyst being 60 to 100 m 2 / g, the average pore diameter is 5 to 10 nm, and in the infrared spectrum of the acrylonitrile catalyst, 2800 cm -1 ~3000cm -1 There are no characteristic peaks in the range.

[0009] Furthermore, based on the weight of the catalyst, the content of the metal oxide is 30% to 70%, preferably 45% to 55%, and the content of the carrier component is 70% to 30%, preferably 55% to 45%.

[0010] Furthermore, based on the weight of the catalyst, the weight percentage of Mo calculated as MoO3 is 15% to 40%, preferably 22% to 30%, the weight percentage of Bi calculated as Bi2O3 is 1.0% to 4.0%, preferably 1.5% to 3.0%, and the weight percentage of Fe calculated as Fe2O3 is 2.0% to 6.0%, preferably 3.0% to 5.0%.

[0011] Furthermore, the metal oxide may also include one or more oxides of Ni, Ce and Mg; based on the weight of the catalyst, the total content of Ni, Ce and Mg in terms of oxides is 12% to 20%.

[0012] Furthermore, the silicon-based porous carrier includes one or more of silicon dioxide and silicon dioxide-alumina, preferably silicon dioxide.

[0013] Furthermore, the catalyst of the present invention was characterized by infrared spectroscopy. -1 ~300cm -1 There are no characteristic peaks in the range, indicating that the organic template introduced in the catalyst preparation has been completely removed and there is no organic template or its carbonization product.

[0014] Furthermore, when the catalyst of the present invention is used for preparing acrylonitrile by ammoxidation of propylene, after running for 500 to 1000 hours under conventional conditions in the field, the Fe in the catalyst is all trivalent Fe. According to XRD characterization, the trivalent Fe component at 23.3° in the active component is well preserved, and no divalent Fe component at 26.5° after reduction appears.

[0015] The second aspect of the present invention provides a method for preparing a catalyst for preparing acrylonitrile by propylene ammoxidation, comprising:

[0016] (a) mixing a precursor containing an active metal element, an organic template, water and a carrier precursor to obtain a slurry, and then drying to obtain a granular material;

[0017] (b) mixing the granules obtained in step (a) with peroxide particles and then calcining;

[0018] (c) After calcination, the peroxide particles and the reacted substances are removed to obtain an acrylonitrile catalyst.

[0019] Furthermore, the specific process of step (a) can be: dissolving the precursor containing active metal elements and the organic template in water respectively, then mixing them evenly with the carrier precursor, stirring them under heating to obtain slurry, and then drying them to obtain particles.

[0020] Furthermore, in step (a), the precursor containing active metal elements is a water-soluble salt containing active metal elements, wherein the precursor containing Mo is one or more of a water-soluble inorganic acid salt containing Mo, a water-soluble organic acid salt containing Mo, or an oxygen-containing acid ammonium salt containing Mo, preferably an oxygen-containing acid ammonium salt containing Mo, such as (NH4)6Mo7O 24 Or its hydrate. The remaining precursors containing active metal elements are preferably one or more of water-soluble inorganic acid salts and water-soluble organic acid salts of the corresponding active metal elements, more preferably one or more of halides, alkoxides, nitrates or acetates, especially nitrates. Such as bismuth nitrate, iron nitrate, nickel nitrate, magnesium nitrate.

[0021] Furthermore, in step (a), the dissolution can be carried out at a conventional temperature in the art until sufficient dissolution is achieved.

[0022] Furthermore, in step (a), the carrier precursor is a conventional carrier precursor in the art, such as one or more of silica sol, silicate, silicate, organosilane, aluminosilicate, or at least one of the above carrier precursors and alumina sol.

[0023] Furthermore, in step (a), the organic template is selected from one or more of small molecule organic acids, amphiphilic alkyl quaternary ammonium salts or polyether amphiphilic block copolymers, such as one or more of cetyltrimethylammonium bromide, citric acid or tartaric acid. The mass ratio of the organic template to the carrier precursor is 0.005:1 to 0.05:1.

[0024] Furthermore, in step (a), the mixing is carried out under heating conditions, wherein the heating temperature is 100-150° C., the stirring speed is 300-450 rpm, and the stirring time is 0.5-2.5 h.

[0025] Furthermore, in step (a), the drying is spray drying, the heat source is air, the drying temperature is 200-480°C, preferably 300-400°C, the drying time is 0.5-4h, preferably 0.5-1.5h, and the average diameter of the spray droplets is 40-200μm, preferably 60-180μm.

[0026] Furthermore, in step (b), the peroxide comprises one or more of calcium peroxide and barium peroxide. The size of the peroxide particles is 20-40 mesh.

[0027] Furthermore, in step (b), the mass ratio of the added peroxide particles to the particles obtained in step (a) is 1:15 to 1:8.

[0028] Furthermore, in step (b), the mixing can be carried out by conventional mechanical mixing to achieve uniform mixing.

[0029] Furthermore, in step (b), the calcination conditions are: calcination in an oxygen-containing atmosphere, such as calcination in an air atmosphere; the calcination temperature is 200-700° C., preferably 400-650° C., and the calcination time is 3-8 hours, preferably 4-6 hours.

[0030] Furthermore, in step (c), the substance obtained after the reaction of the peroxide particles mainly refers to the corresponding oxide obtained after calcination.

[0031] Furthermore, in step (c), the method for removing the peroxide particles and the substances after the reaction is to separate them by sieving through a sample sieve, and the mesh number of the sample sieve is greater than 40 meshes to ensure that the peroxide particles can be completely separated from the catalyst.

[0032] Furthermore, the active metal elements include at least Mo, Bi and Fe. Based on the weight of the obtained catalyst, the final content of the metal oxide is 30% to 70%, preferably 45% to 55%, and the content of the carrier component is 70% to 30%, preferably 55% to 45%.

[0033] Furthermore, based on the weight of the catalyst, the weight percentage of Mo calculated as MoO3 is 15% to 40%, preferably 22% to 30%, the weight percentage of Bi calculated as Bi2O3 is 1.0% to 4.0%, preferably 1.5% to 3.0%, and the weight percentage of Fe calculated as Fe2O3 is 2.0% to 6.0%, preferably 3.0% to 5.0%.

[0034] Furthermore, the active metal element may also include one or more of Ni, Ce and Mg; based on the weight of the catalyst, the total content of Ni, Ce and Mg in terms of oxides is 12% to 20%.

[0035] A third aspect of the present invention provides use of the above catalyst or the catalyst prepared by the above method in preparing acrylonitrile by ammoxidation of propylene.

[0036] The application is specifically as follows: in the presence of the catalyst, propylene undergoes an ammoxidation reaction in the presence of ammonia and oxygen to generate acrylonitrile.

[0037] The specific reaction conditions include: the molar ratio of propylene / ammonia / air (based on the oxygen contained) is 1:1.2-1.3:9.6-10.0, the reaction temperature is 420-435°C, the reaction pressure (gauge pressure) is 0.06-0.14 MPa, and the weight hourly space velocity is 0.06-0.10 h -1 .

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] The catalyst for preparing acrylonitrile by propylene ammoxidation of the present invention has simple components and can maintain a high acrylonitrile per-pass yield for a long time. After long-term operation, it can still maintain a high propylene conversion rate and acrylonitrile per-pass yield.

[0040] The catalyst for preparing acrylonitrile by propylene ammoxidation of the present invention can completely remove the organic template agent and its carbonized product added before after calcination, and the obtained catalyst has a high specific surface area and a suitable pore size distribution. However, in the catalyst prepared by the prior art, if the organic template agent is added during the preparation process, it cannot be completely removed after calcination, and there will be residual carbonized products.

[0041] The method for preparing a catalyst for preparing acrylonitrile by propylene ammoxidation of the present invention comprises mixing peroxide particles with a catalyst precursor and calcining them together, which can not only completely remove the organic template but also deeply oxidize the active components. Compared with the acrylonitrile catalyst obtained by the traditional calcination method, the catalyst has good long-term operation stability.

[0042] The catalyst for preparing acrylonitrile by propylene ammoxidation prepared by the prior art contains metals in the highest valence state at the initial stage of the reaction. However, after running for a period of time (such as 500 hours), trivalent iron will be reduced to divalent iron, thereby affecting the activity and selectivity of the catalyst. However, the catalyst for preparing acrylonitrile by propylene ammoxidation obtained by the preparation method of the present invention still has the highest valence state of the metal after a long period of operation (such as 500 hours), such as Fe is still trivalent. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is the infrared spectrum of the catalyst obtained in Example 1;

[0044] Figure 2This is the XRD spectrum of the catalyst obtained in Example 1 after running for 500 hours;

[0045] Figure 3 is the infrared spectrum of the catalyst obtained in Comparative Example 1;

[0046] Figure 4 This is the XRD spectrum of the catalyst obtained in Comparative Example 1 after running for 500 hours. DETAILED DESCRIPTION

[0047] In the present invention, the specific surface area and pore size are measured by a Tristar physical adsorption instrument. Before the sample is tested, it is necessary to perform a heating vacuum degassing treatment. The porosity of the sample is measured at 77K, and the specific surface area is calculated by the Brunauer-Emmett-Teller (BET) method. The pore size distribution and pore volume can be calculated from the isothermal adsorption branch using the Barrettner-Joyner-Halenda (BJH) model.

[0048] In the present invention, the X-ray diffraction is measured using a Bruker D4 XRD powder tester produced in Germany, and the test conditions are 40 kV and 40 mA.

[0049] In the present invention, the Fourier transform infrared (FT-IR) spectrum used is a Nicolet Fourier spectrophotometer manufactured in the United States.

[0050] In the present invention, gas chromatography is used to perform online analysis on the product gas, and the conversion rate of propylene, the selectivity of acrylonitrile and the single-pass yield are used as indicators for evaluating the performance of the catalyst, and the definitions of the two are as follows:

[0051] Propylene conversion (%) = (moles of propylene reacted / moles of propylene fed) × 100%,

[0052] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene reacted) × 100%,

[0053] Acrylonitrile single-pass yield (%) = (number of moles of acrylonitrile produced / number of moles of propylene fed) × 100%.

[0054] [Example 1]

[0055] (1) Preparation of catalyst

[0056] 63.25 g (NH4)6Mo7O 24·4H2O was heated and dissolved in water to obtain solution I; 9.60 g Bi(NO3)3·5H2O, 68.31 g Ni(NO3)2·6H2O, 33.22 g Fe(NO3)3·9H2O, and 23.35 g Mg(NO3)2·6H2O were dissolved in water to obtain solution II. 2.8 g CTAB was dissolved in water to obtain solution III. 220 g silica sol with a mass fraction of 40% and solution III were added to solution I, and solution II was added after uniform stirring, and stirred at a stirring speed of 200 rpm at 100°C for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 h. The average diameter of the spray droplets was 90 μm to obtain particles.

[0057] The particles obtained by spray drying were uniformly mixed with 20-mesh calcium peroxide particles at a weight ratio of 10:1, and calcined at 600°C for 3 hours in an air atmosphere to obtain a mixed particle. The mixed particle was sieved through a 60-mesh sample sieve to separate the large-size residual calcium peroxide particles after calcination to obtain the final catalyst A. The specific surface area of ​​the catalyst was 64.8 m 2 / g, and the average pore diameter is 7.6nm.

[0058] The catalyst was characterized by infrared spectroscopy (see Figure 1 ), found 2900cm -1 The characteristic peak of the organic template has completely disappeared, indicating that the CTAB template has been completely removed after calcination.

[0059] (2) Catalyst activity evaluation

[0060] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085MPa; catalyst loading: 300g; catalyst propylene load (WWH): 0.06h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.82%, the acrylonitrile selectivity was 84.90%, and the acrylonitrile single-pass yield was 83.90%. After 500 hours of operation, the propylene conversion rate was 98.56%, the acrylonitrile selectivity was 84.51%, and the acrylonitrile single-pass yield was 83.29%.

[0061] XRD analysis of the catalyst sample taken after 500 hours of operation revealed that Figure 2), the trivalent Fe component at about 23.3° in the active component is well preserved, and the divalent Fe component at about 26.5° after reduction does not appear, indicating that after long-term operation, the catalyst still maintains good stability and oxidation activity.

[0062] [Example 2]

[0063] (1) Preparation of catalyst

[0064] 63.25 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.60 g Bi(NO3)3·5H2O, 68.31 g Ni(NO3)2·6H2O, 33.22 g Fe(NO3)3·9H2O, and 23.35 g Mg(NO3)2·6H2O were dissolved in water to obtain solution II. 2.8 g citric acid was dissolved in water to obtain solution III. 220 g silica sol with a mass fraction of 40% and solution III were added to phase solution I in sequence, and solution II was added after uniform stirring, and stirred at a stirring speed of 200 rpm at 100°C for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 h. The average diameter of the spray droplets was 90 μm to obtain particles.

[0065] The particles obtained by spray drying were uniformly mixed with 20-mesh calcium peroxide particles in a ratio of 12:1, and calcined at 600°C for 3 hours in an air atmosphere to obtain a mixed particle. The mixed particle was sieved through a 60-mesh sieve to separate the large-size residual calcium peroxide particles after calcination to obtain the final catalyst B. The specific surface area of ​​the catalyst was 62.7 m 2 / g, and the average pore diameter is 7.9nm.

[0066] The catalyst was characterized by infrared spectroscopy. Figure 1 , 2900cm -1 The characteristic peak of the organic template has completely disappeared, indicating that the organic template has been completely removed after calcination.

[0067] (2) Catalyst activity evaluation

[0068] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst were the same as those in Example 1. After 3 hours of operation, the propylene conversion was 98.76%, the acrylonitrile selectivity was 84.75%, and the acrylonitrile per pass yield was 83.70%. After 500 hours of operation, the propylene conversion was 98.45%, the acrylonitrile selectivity was 84.53%, and the acrylonitrile per pass yield was 83.22%.

[0069] XRD analysis of the catalyst sample taken after 500 hours of operation revealed that (similar to Figure 2), the trivalent Fe component at about 23.3° in the active component is well preserved, and the divalent Fe component at about 26.5° after reduction does not appear, indicating that after long-term operation, the catalyst still maintains good stability and oxidation activity.

[0070] [Example 3]

[0071] (1) Preparation of catalyst

[0072] 63.25 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.60 g Bi(NO3)3·5H2O, 68.31 g Ni(NO3)2·6H2O, 33.22 g Fe(NO3)3·9H2O, and 23.35 g Mg(NO3)2·6H2O were dissolved in water to obtain solution II. 5.6 g CTAB was dissolved in water to obtain solution III. 220 g silica sol with a mass fraction of 40% and solution III were added to phase solution I in sequence, and solution II was added after uniform stirring, and stirred at a stirring speed of 200 rpm at 100°C for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 h. The average diameter of the spray droplets was 90 μm to obtain particles.

[0073] The particles obtained by spray drying were uniformly mixed with 20-mesh barium peroxide particles in a ratio of 10:1, and calcined at 600°C for 3 hours in an air atmosphere to obtain a mixed particle. The mixed particle was passed through a 60-mesh sieve to separate the large-size residual calcium peroxide particles after calcination to obtain the final catalyst C, with a specific surface area of ​​66.7 m 2 / g, and the average pore diameter is 6.5nm.

[0074] The infrared characterization of the catalyst is similar to Figure 1 , 2900cm -1 The characteristic peak of the organic template has completely disappeared, indicating that the CTAB template has been completely removed after calcination.

[0075] (2) Catalyst activity evaluation

[0076] The reaction conditions for producing acrylonitrile by ammoxidation of propylene with the above catalyst were the same as those in Example 1. After 3 hours of operation, the propylene conversion was 98.74%, the acrylonitrile selectivity was 84.56%, and the acrylonitrile per pass yield was 83.49%. After 500 hours of operation, the propylene conversion was 98.45%, the acrylonitrile selectivity was 84.35%, and the acrylonitrile per pass yield was 83.04%.

[0077] XRD analysis of the catalyst sample taken after 500 hours of operation revealed that (similar to Figure 2 ), the trivalent Fe component at about 23.3° in the active component is well preserved, and the divalent Fe component at about 26.5° after reduction does not appear, indicating that after long-term operation, the catalyst still maintains good stability and oxidation activity.

[0078] [Example 4]

[0079] (1) Preparation of catalyst

[0080] 63.25 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.60 g Bi(NO3)3·5H2O, 68.31 g Ni(NO3)2·6H2O, 33.22 g Fe(NO3)3·9H2O, and 23.35 g Mg(NO3)2·6H2O were dissolved in water to obtain solution II. 3.5 g tartaric acid was dissolved in water to obtain solution III. 220 g silica sol with a mass fraction of 30% and solution III were added to solution I, and solution II was added after uniform stirring, and stirred at a stirring speed of 200 rpm at 100°C for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 380°C and a drying time of 1h. The average diameter of the spray droplets was 90μm to obtain particles.

[0081] The particles obtained by spray drying were uniformly mixed with 20-mesh calcium peroxide particles at a weight ratio of 10:1, and calcined at 650°C for 3 hours in an air atmosphere to obtain a mixed particle. The mixed particle was sieved through a 60-mesh sieve to separate the large-size residual calcium peroxide particles after calcination to obtain the final catalyst D. The specific surface area of ​​the catalyst was 71.8 m 2 / g, and the average pore diameter is 6.6nm.

[0082] The catalyst was characterized by infrared spectroscopy. Figure 1 , 2900cm -1 The characteristic peak of the organic template has completely disappeared, indicating that the organic template has been completely removed after calcination.

[0083] (2) Catalyst activity evaluation

[0084] The reaction conditions for producing acrylonitrile by ammoxidation of propylene with the above catalyst were the same as those in Example 1. After 3 hours of operation, the propylene conversion was 98.65%, the acrylonitrile selectivity was 84.70%, and the acrylonitrile per pass yield was 83.56%. After 500 hours of operation, the propylene conversion was 98.41%, the acrylonitrile selectivity was 84.26%, and the acrylonitrile per pass yield was 82.91%.

[0085] XRD analysis of the catalyst sample taken after 500 hours of operation revealed that (similar to Figure 2 ), the trivalent Fe component at about 23.3° in the active component is well preserved, and the divalent Fe component at about 26.5° after reduction does not appear, indicating that after long-term operation, the catalyst still maintains good stability and oxidation activity.

[0086] [Comparative Example 1]

[0087] (1) Preparation of catalyst

[0088] 63.25 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.60 g Bi(NO3)3·5H2O, 68.31 g Ni(NO3)2·6H2O, 33.22 g Fe(NO3)3·9H2O, and 23.35 g Mg(NO3)2·6H2O were dissolved in water to obtain solution II. 2.8 g CTAB was dissolved in water to obtain solution III. 300 g of 40% silica sol and solution III were added to phase solution I in sequence, and solution II was added after uniform stirring. The mixture was stirred at 200 rpm and at 100°C for 0.5 hours to obtain a slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 h. The average diameter of the spray droplets was 90 μm to obtain particles. The particles were calcined at 600°C in an air atmosphere for 3 hours to obtain catalyst F. The specific surface area of ​​the catalyst was 45.3 m 2 / g, and the average pore diameter is 11.6nm.

[0089] The catalyst was characterized by infrared spectroscopy (see Figure 3 ), found 2921cm -1 and 2851cm -1 There are residual characteristic peaks of organic template at , indicating that the CTAB template is not completely removed after calcination.

[0090] (2) Catalyst activity evaluation

[0091] The reaction conditions for the above catalyst to produce acrylonitrile by ammoxidation of propylene were the same as those in Example 1. After 3 hours of operation, the propylene conversion was 97.76%, the acrylonitrile selectivity was 82.40%, and the acrylonitrile per pass yield was 80.55%. After 500 hours of operation, the propylene conversion was 95.22%, the acrylonitrile selectivity was 81.14%, and the acrylonitrile per pass yield was 77.26%. The XRD analysis of the catalyst sampled after 500 hours of operation revealed that (see Figure 4), the content of trivalent Fe component at about 23.3° in the active component was significantly reduced. Quantitative analysis by XRD found that the content of trivalent Fe component was reduced by about 45% compared with the fresh agent. At the same time, divalent Fe component appeared at about 26.5° after reduction, indicating that after long-term operation, the active oxidation components of the catalyst were lost more, resulting in a significant decrease in its activity.

[0092] [Comparative Example 2]

[0093] (1) Preparation of catalyst

[0094] 63.25 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.60 g Bi(NO3)3·5H2O, 68.31 g Ni(NO3)2·6H2O, 33.22 g Fe(NO3)3·9H2O, and 23.35 g Mg(NO3)2·6H2O were dissolved in water to obtain solution II. 2.8 g CTAB was dissolved in water to obtain solution III. 300 g of 40% silica sol and solution III were added to phase solution I, and solution II was added after uniform stirring. The mixture was stirred at 200 rpm and at 100°C for 0.5 hours to obtain a slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 h. The average diameter of the spray droplets was 90 μm to obtain particles. The particles were calcined at 600°C for 3 hours in an oxygen atmosphere with a purity of 99.9% to obtain catalyst G. The specific surface area of ​​the catalyst was 46.3 m 2 / g, and the average pore diameter is 12.0nm.

[0095] (2) Catalyst activity evaluation

[0096] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation were the same as those in Example 1. After 3 hours of operation, the propylene conversion was 98.31%, the acrylonitrile selectivity was 83.65%, and the acrylonitrile per pass yield was 82.24%. After 500 hours of operation, the propylene conversion was 97.26%, the acrylonitrile selectivity was 83.01%, and the acrylonitrile per pass yield was 80.74%.

Claims

1. A catalyst for preparing acrylonitrile by ammoxidation of propylene, characterized in that: The catalyst comprises a metal oxide and a carrier component, wherein the carrier component is a silicon-based porous carrier, the metal oxide comprises at least oxides of three active metal elements: Mo, Bi, and Fe, and the specific surface area of ​​the catalyst is 60 to 100 m 2 / g, an average pore diameter of 5-10nm, and an infrared spectrum of 2800cm -1 ~3000cm -1 There are no characteristic peaks in the range; The catalyst is prepared by mixing peroxide particles with a catalyst precursor and calcining the mixture together to completely remove the organic template, wherein the peroxide comprises one or more of calcium peroxide and barium peroxide.

2. The catalyst according to claim 1, characterized in that: Based on the weight of the catalyst, the content of the metal oxide is 30% to 70%, and the content of the carrier component is 70% to 30%.

3. The catalyst according to claim 2, characterized in that: Based on the weight of the catalyst, the content of the metal oxide is 45% to 55%, and the content of the carrier component is 55% to 45%.

4. The catalyst according to claim 1 or 2, characterized in that: Based on the weight of the catalyst, the weight percentage of Mo calculated as MoO3 is 15% to 40%, the weight percentage of Bi calculated as Bi2O3 is 1.0% to 4.0%, and the weight percentage of Fe calculated as Fe2O3 is 2.0% to 6.0%.

5. The catalyst according to claim 4, characterized in that: Based on the weight of the catalyst, the weight percentage of Mo calculated as MoO3 is 22% to 30%, the weight percentage of Bi calculated as Bi2O3 is 1.5% to 3.0%, and the weight percentage of Fe calculated as Fe2O3 is 3.0% to 5.0%.

6. The catalyst according to claim 4, characterized in that: The metal oxide component also includes one or more of Ni, Ce and Mg; based on the weight of the catalyst, the total content of Ni, Ce and Mg in terms of oxides is 12% to 20%.

7. The catalyst according to claim 1, characterized in that: The silicon-based porous carrier includes one or more of silicon dioxide and silicon dioxide-alumina.

8. A method for preparing a catalyst according to any one of claims 1 to 7, comprising the following steps: (a) mixing a precursor containing an active metal element, an organic template, water and a carrier precursor to obtain a slurry, and then drying to obtain particles; (b) mixing the granules obtained in step (a) with peroxide particles and then calcining; (c) after calcination, removing the peroxide particles and the reacted substances to obtain a catalyst; In step (b), the peroxide includes one or more of calcium peroxide and barium peroxide.

9. The method according to claim 8, characterized in that: In step (a), the precursor containing the active metal element is a water-soluble salt containing the active metal element.

10. The method according to claim 8, characterized in that: In step (a), the carrier precursor is one or more of silica sol, silicate, silicate ester, organosilane, aluminosilicate, or at least one of the above carrier precursors and alumina sol.

11. The method according to claim 8, characterized in that: In step (a), the organic template is selected from one or more of small molecule organic acids, amphiphilic alkyl quaternary ammonium salts or polyether amphiphilic block copolymers; the mass ratio of the organic template to the carrier precursor is 0.005:1 to 0.05:

1.

12. The method according to claim 11, characterized in that: In step (a), the organic template is selected from one or more of cetyltrimethylammonium bromide, citric acid or tartaric acid.

13. The method according to claim 8, characterized in that: In step (a), the mixing is performed under heating conditions, wherein the heating temperature is 100-150° C., the stirring speed is 300-450 rpm, and the stirring time is 0.5-2.5 h.

14. The method according to claim 8, characterized in that: In step (a), the drying is spray drying, the drying temperature is 200-480° C., the drying time is 0.5-4 hours, and the average diameter of the spray droplets is 40-200 μm.

15. The method according to claim 14, characterized in that: In step (a), the drying temperature is 300-400° C., the drying time is 0.5-1.5 h, and the average diameter of the spray droplets is 60-180 μm.

16. The method according to claim 8, characterized in that: In step (b), the size of the peroxide particles is 20-40 mesh.

17. The method according to claim 8, characterized in that: In step (b), the mass ratio of the added peroxide particles to the particles obtained in step (a) is 1:15 to 1:

8.

18. The method according to claim 8, characterized in that: In step (b), the calcination conditions are: calcination in an oxygen-containing atmosphere, a calcination temperature of 200-700° C., and a calcination time of 3-8 hours.

19. The method according to claim 18, characterized in that: In step (b), the calcination conditions are: calcination temperature is 400-650° C., and calcination time is 4-6 hours.

20. Use of the catalyst according to any one of claims 1 to 7 or the catalyst prepared by the method according to any one of claims 8 to 19 in preparing acrylonitrile by ammoxidation of propylene.

Citation Information

Patent Citations

  • Unsaturated nitrile fluidized bed catalyst prepared by ammoxidation and its preparation method

    CN102371156A

  • Ammoxidation of olefin to unsaturated nitrile fluid catalyst and preparation method thereof

    CN105195165A

  • Acrylonitrile catalyst and preparation method and application thereof

    CN109772356A

  • Ammoxidation catalyst particles as well as preparation method and application thereof

    CN111744493A